2002
DOI: 10.1080/01650250143000373
|View full text |Cite
|
Sign up to set email alerts
|

Development of lying to conceal a transgression: Children’s control of expressive behaviour during verbal deception

Abstract: T he present study examined lying behaviour in children between 3 and 7 years of age with two experiments. A temptation resistance paradigm was used in which children were left alone in a room with a music-playing toy placed behind their back. T he children were told not to peek at the toy. Most children could not resist the temptation and peeked at the toy. When the experimenter asked them whether they had peeked, about half of the 3-year-olds confessed to their transgression, whereas most older children lied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

52
409
11
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(485 citation statements)
references
References 34 publications
52
409
11
13
Order By: Relevance
“…One of the first paradigms used was a temptation resistance paradigm, was originally pioneered by Sears, Rau, and Alpert (1965), and has been subsequently modified to examine children"s antisocial lies Talwar & Lee, 2002a). During the temptation resistance paradigm, children are instructed not to peek at a toy while an experimenter is out of the room.…”
Section: Lie-telling Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first paradigms used was a temptation resistance paradigm, was originally pioneered by Sears, Rau, and Alpert (1965), and has been subsequently modified to examine children"s antisocial lies Talwar & Lee, 2002a). During the temptation resistance paradigm, children are instructed not to peek at a toy while an experimenter is out of the room.…”
Section: Lie-telling Developmentmentioning
confidence: 99%
“…In another study, Talwar and Lee (2002a) examined 3-to 7-year-old"s lie-telling behaviours using a modified temptation resistance paradigm. Similar to , they examined whether children would tell a lie to conceal a transgression and examined children"s ability to maintain their lie through follow-up questioning.…”
Section: Lie-telling Developmentmentioning
confidence: 99%
“…secrets, both spontaneously and when asked to do so by an adult (e.g., Bottoms, Goodman, Schwartz-Kenney, & Thomas, 2002;Talwar & Lee, 2002;Wilson & Pipe, 1989). Moreover, by age 6, children can provide false statements to back up their secrets (Tye, Amato, Honts, Devitt, & Peters, 1999).…”
mentioning
confidence: 99%
“…Third, it is possible that children learn to associate avoidant gaze with lying from their direct experience of deception "in the playground." Although young children and adults do not appear to avoid mutual gaze when they lie (Kleinke, 1986;Lewis, Stranger, & Sullivan, 1989;Talwar & Lee, 2002), a recent study has found that 7-to 9-year-olds do display this behavior (McCarthy, Muir, & Lee, 2007). Accordingly, at 9 years old, children will have had greater opportunity to observe the co-occurrence of gaze aversion and lying in their peers than at 6 years old.…”
Section: Discussionmentioning
confidence: 99%